Analisis Konfigurasi Tunnel IPv6, Auto Tunnel, dan ISATAP dalam Pembangunan Infrastruktur Jaringan - Akbar, Yuma; Setiawan, Kiki; Aula, Raisah Fajri; Aimar, Muqorrobin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
IP (Internet Protocol) is needed to be the address of a device that wants to connect to each other, whether connected locally or to the internet. As technology develops, IP addressing allocation becomes increasingly necessary. The IP address that is often used is IPv4, but IPv4 allocation is increasingly limited. For this reason, a renewable IP version was created, namely IPv6. IPv6 itself has many advantages in terms of security which is equipped with encryption, then in terms of effectiveness in configuration which can use Auto Config, as well as a larger number of allocations compared to IPv4. If IPv4 only uses 32 bits, IPv6 uses 128 bits, for this reason the number of allocations given by IPv6 is much greater. This amount should be able to cover the lack of allocation from IPv4. Therefore, IPv4 to IPv6 migration must be carried out slowly, in-order-to overcome the lack of allocation in IPv4. Fortunately, IPv6 tunneling can run in parallel with IPv4 without disrupting existing infrastructure. Where IPv4 can be used as an Underlay Network (a network that is the foundation of the virtual network above it), and IPv6 will be an Overlay Network (a virtual network that connects users as if they were connected directly, this virtual network must be built on top of the Underlay Network, in this case the IPv6 tunnel will be used as a virtual network).